Stereotyp w słusznej sprawie, czyli „brulionowa” podróż na południe - Jakub Suliga (Studia Slavica)
The article concerns the Polish stereotype of the Czech and its transformation with the help of literature. An analysis of illegal periodicals has shown that in the 1980s there were two strategies at work in Polish samizdat: the first attempted to adapt the Czechs to the Polish autostereotype, which was a contradiction of the way Poles perceived their southern neighbours. The second strategy was presented by the magazine “brulion”, which broke away from the dominant samizdat model of an ‘engaged press’. The Czech presented in “brulion” fit the stereotype existing in Poland, but, paradoxically, they thus became closer to Poles – the creators and readers of the Krakow magazine, who rejected the heroic autostereotype.